ANALISIS KOMUNIKASI VISUAL DALAM MENINGKATKAN ENGAGEMENT PADA AKUN INSTAGRAM @Kemnaker - Muhamad Reza Pahlevi; Sari Ekowati (Tamilis Synex: Multidimensional Collaboration, 2026)
Instagram social media has become an effective digital communication platform for government institutions in delivering information to the public, including the Ministry of Manpower (Kemnaker) through its Instagram account @kemnaker. This study aims to analyze how visual communication used on the @kemnaker Instagram account can increase audience engagement. Visual communication in this context includes design elements such as the use of color, typography, illustration, photography, and content layout. This research uses a qualitative approach with a descriptive analysis method. Data were collected through observation of Instagram content on @kemnaker, documentation of posts, and interviews with social media managers. The data analysis technique was conducted by identifying visual communication elements and relating them to engagement levels such as likes, comments, shares, and saves. The results show that consistent, informative, and visually appealing communication plays an important role in increasing user interaction. Content with simple yet communicative design tends to be easier to understand and receives higher responses from audiences. In addition, the use of infographic formats and visual storytelling has proven to be more effective in attracting Instagram users' attention. Thus, it can be concluded that visual communication significantly contributes to increasing engagement on the @kemnaker Instagram account. Therefore, social media managers should continue to optimize visual design strategies in delivering public information.